2021
DOI: 10.1103/physreve.104.l043101
|View full text |Cite
|
Sign up to set email alerts
|

High-speed NMR imaging of capillary action in thin nontransparent porous media

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The current measurement techniques lack the ability to measure below 1 min. Future improvements towards higher time resolutions is, for example, useful in the printing industry where the penetration occurs at timescales of 100 ms. Great potential was shown by R. J. K. Nicasy et al [ 194 ] that demonstrated the use of high-speed NMR to profile liquid uptake in non-transparent porous media with time resolutions of 10 ms. This was only shown for liquid penetration but could be extended towards the characterization of chemical structures.…”
Section: Applicationsmentioning
confidence: 99%
“…The current measurement techniques lack the ability to measure below 1 min. Future improvements towards higher time resolutions is, for example, useful in the printing industry where the penetration occurs at timescales of 100 ms. Great potential was shown by R. J. K. Nicasy et al [ 194 ] that demonstrated the use of high-speed NMR to profile liquid uptake in non-transparent porous media with time resolutions of 10 ms. This was only shown for liquid penetration but could be extended towards the characterization of chemical structures.…”
Section: Applicationsmentioning
confidence: 99%